Long-Term Outcome of Patients Initially Diagnosed With Idiopathic Ventricular Fibrillation: A Descriptive Study. (October 2016) - Visser, Marloes; van der Heijden, Jeroen F.; van der Smagt, Jasper J.; Doevendans, Pieter A.; Wilde, Arthur A.; Loh, Peter; Hassink, Rutger J.
Abstract : Background—: Idiopathic ventricular fibrillation (IVF) is a rare cause of sudden cardiac arrest. Limited data are available on the long-term outcome of IVF patients. Methods and Results—: In this retrospective cohort study, 107 consecutive patients with an initial diagnosis of IVF were analyzed (age at index event 40.4 years, 60% male). Missing diagnostic data were acquired during follow-up, including genetic testing, to exclude underlying disease. A specific diagnosis was revealed in 22 of 107 patients (21%) during a median follow-up of 10.2 years. Mortality rate was 9% in IVF patients (8/85). Appropriate implantable cardioverter–defibrillator therapy was delivered in 23 patients (29%) of 78 IVF patients with an implantable cardioverter–defibrillator, with a median of 3 appropriate shocks per patient. Conclusions—: One fifth of the patients initially diagnosed with IVF reveal a specific diagnosis during long-term follow-up. Additional diagnostic testing, including genetic testing, contributes to the detection of specific diseases. The recurrence rate of ventricular arrhythmias in IVF patients is high. Our data show the importance of thorough follow-up and reassessment of diagnosis in IVF patients. Abstract : Supplemental Digital Content is available in the text.